ON SOME BYZANTINE ELEMENTS IN THE MEDIEVAL ARTS OF DAGESTAN - Mammaev, M M (History, Archeology and Ethnography of the Caucasus, 2015)
Basing on the comparative study of ornament and figural subjects (griffins, eagles) of works of stone carvingart from the villages of Kubachi,Khunzakh and the Byzantine works of applied arts, the author of the article highlights some issues of art links between Dagestan and Byzantium in the 14th – 15th centuries.
Keywords: Dagestan; Kubachi; Khunzakh; Byzantium; similarity of certain ornamental compositions and figural subjects of medieval works of art; art contacts